Recovery and separation of rhenium and molybdenum from aqueous solutions that simulate mine waters using magnetite nanoparticles functionalized with amine-derivative groups. (1st June 2019) - Gaete, José; Molina, Lorena; Alfaro, Ian; Yañez, Joaquin; Valenzuela, Fernando; Basualto, Carlos
Graphical abstract: Highlights: Rhenium and molybdenum are recovered from acidic solutions using an adsorption process. Adsorbents are based on magnetic nanoparticles functionalized with amine groups. The adsorbent compounds were synthesized and chemically and physically characterized. The used adsorbents uptake Re(VII) and Mo(VI) based on an anionic exchange mechanism. The adsorbents presented a higher adsorption towards Mo(VI) respect to Re(VII). Abstract: The recovery and separation of rhenium and molybdenum from acidic aqueous solutions that simulate mine waters is studied through an adsorption process using magnetite nanoparticles functionalized with tertiary (TA-MNP) and quaternary amine (QA-MNP) groups as adsorbents. The functionalized nanoparticles (FMNP) were efficiently synthetized and physical and chemically characterized. An average particle size in the range of 6–8 nm based on HR-TEM analysis was determined for the nanoparticles, which exhibited a high saturation magnetization varying between 53 and 60 emu/g. Several factors that affected the recovery of Re(VII) and Mo(VI) from aqueous solution using the synthesized FMNP were studied, such as the adsorbent dose, initial concentration of metal and pH of the aqueous feed solution. In all experiments, QA-MNP presented a slightly better adsorption of both metals compared to TA-MNP. At pH 3, maximum rhenium loading capacities of 30 and 38 mgRe(VII) /gadsorbent were measured using TA-MNP and QA-MNP, respectively. In turn, maximum loading capacities of 60 and 65 mgMo(VI) /gadsorbent were determined utilizing TA-MNP and QA-MNP, respectively. Re(VII) and Mo(VI) equilibrium and kinetics were established in adsorption experiments. A pseudo-second-order kinetic model provided a good fit to the experimental data for the two metals using both adsorbents. Freundlich and Langmuir adsorption isotherm explained the experimental results.